2013
DOI: 10.1021/ct400465q
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation to the Gold-Standard in Quantum Chemistry: Computationally Efficient and Accurate CCSD(T) Energies for Large Molecules Using an Automated Thermochemical Hierarchy

Abstract: The CCSD(T) method is known as the gold-standard in quantum chemistry and has been the method of choice in quantum chemistry for over 20 years to obtain accurate bond energies and molecular properties. Its computational cost formally scales as the seventh power of the size of the system and can be prohibitive for large molecules. As part of our efforts to reduce the computational cost of the CCSD(T) method yet retain its accuracy, we present a simple, efficient, and user-friendly protocol to extrapolate to CCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 140 publications
2
121
0
Order By: Relevance
“…41 To illustrate the use of CBH as a fragment-based method, we hereafter loosely use the phrase "fragments" to allude to the "reference molecules" in the CBH scheme (i.e., both primary and derivative subsystems).…”
Section: A New Concept In Fragment-based Methods As a Results Of Its Mmentioning
confidence: 99%
See 1 more Smart Citation
“…41 To illustrate the use of CBH as a fragment-based method, we hereafter loosely use the phrase "fragments" to allude to the "reference molecules" in the CBH scheme (i.e., both primary and derivative subsystems).…”
Section: A New Concept In Fragment-based Methods As a Results Of Its Mmentioning
confidence: 99%
“…Yet, sub-kilocalorie per mole accuracy is achieved with the ring form and the open form (Table 2), thus showcasing the success of our method. More detailed insights on the individual performance of some of the other molecules in the test set, extrapolated CCSD energies, and the poor performance with the CBH-1 rung (thus testifying the need for appropriate error cancellation from CBH-2 and higher rungs) are given in ref 41. It should also be emphasized here that the current formulation of CBH as a fragment-based method is applicable only for energetic minima on the potential energy surface since the fragment energies are constant and do not vary as the geometry of the parent molecule changes.…”
Section: A New Concept In Fragment-based Methods As a Results Of Its Mmentioning
confidence: 99%
“…CCSD(T) is generally considered as “gold standard” . By comparing Table with Table S2 (Supporting Information), we can see that the performance of the single‐point‐energy calculations at the CCSD level [without (T)] is actually not that close to those at the CCSD(T) level.…”
Section: Resultsmentioning
confidence: 99%
“…At CBH‐3, the immediate chemical environments of all the heavy atom bonds are preserved. As the name suggests, at higher level of rungs a greater chemical environment (and a geometry more similar to parent molecule) is preserved, and results in accurate thermochemistry, and an accurate extrapolation to CCSD(T) energies …”
Section: Methodology and Comparison With Other Fragment‐based Methodsmentioning
confidence: 99%
“…For a range of organic and bio‐organic molecules in these studies, it was observed that the MP2 and CCSD(T) reaction energies were in close agreement for CBH‐2 reaction schemes. This allowed the use of MP2 energy and CCSD(T) energies of fragments to extrapolate to the CCSD(T) energy of the target molecule . For the sake of brevity, the method is only discussed briefly in the methodology section, while complete details of the method can be found in the previous work, and a recent review .…”
Section: Introductionmentioning
confidence: 99%